Manajemen Kepala Sekolah Negeri dalam Meningkatkan Mutu Pendidikan (Studi di SMA Negeri 2 Lawe Sigala-Gala Aceh Tenggara) - Barutu, Zulyadin; Prasetia, Indra; Sulasmi, Emilda (UMSU, 2024)
The aim of this research is: (1). To find out how the principal plans to improve the quality of education in terms of student achievement at SMA Negeri 2 Lawe Sigala-gala Babul Makmur Subdistrict Southeast Aceh District. (2). To find out how the principal organizes in improving the quality of education in terms of student achievement at SMA Negeri 2 Lawe Sigala-gala Babul Makmur Subdistrict Southeast Aceh District. (3). To find out how the principal’s implementation is in improving the quality of education in terms ofstudent achievement at SMA Negeri 2 Lawe Sigala-gala Babul Makmur Subdistrict Southeast Aceh District. This research uses a qualitative method with a descriptive approach. Data collection techniques use observation, interviews and documentation. Data analysis is used by: data reduction, data presentation and drawing conclusions. Checking the validity of the data is carried out by observation, triangulation and adequacy of references. Based on the research results it was found : (1). The planning carried out by the chool principal is to implement 8 educational standards, do not force students to excel if it does not match their abilities. (2). The organization carried out by the school principal is to group high-achieving students by identifying high-achieving students from the beginning of the entry of new students using an approach. (3). The implementation carried out by the school principal involves the participation of student parents to improve student achievement, carryout activities in accordance with the scool budget work plan and in developing students, the participal directly involves teachers who have competencies in accordance with their respective fields at the school.